Association Between Colistin Dose and Development of Nephrotoxicity. Issue 2 (April 2016) - Lee, Yu-Ji; Wi, Yu Mi; Kwon, Yun Jae; Kim, Sung Rok; Chang, Se-Ho; Cho, Seong
Abstract : Surv Anesthesiol 2016;60(2):57–57 The increasing prevalence of the extensively drug-resistant (XDR) bacteria Pseudomonas aeruginosa and Acinetobacter baumannii has been associated with higher global rates of morbidity and mortality. In the absence of any newer antimicrobial agents to combat XDR gram-negative microorganisms, colistin has been widely reused to treat infections caused by XDR Pseudomonas and Acinetobacter, but concerns about nephrotoxicity, a well-known adverse effect of colistin, have limited the use of this drug.